Priorities for Bolstering Public Health Resilience in the Context of Climate Change in Dominica and Puerto Rico - Hannah H. Covert; Lissa Fortes Soares; Firoz Abdoel Wahid; Teddy Allen; Zack Guido; David Johnson; Roché Mahon; Pablo Méndez-Lázaro; Mya Sherman; Sylvester St. Ville; Adrian Trotman; Maureen Y. Lichtveld (Ubiquity Press, 2022)
Caribbean small island developing states are highly exposed to climate change impacts. Incorporating weather and climate information into public health decisions can promote resilience to climate change's adverse health effects, but regionally it is not common practice. We implemented a project to enhance dialogue between climate and public health specialists in Puerto Rico and Dominica. First, we conducted environmental scans of public health vulnerability in the context of weather and climate for both islands. Then, we convened stakeholders to discuss the scan results and identify priorities for climate and health. A shared priority was increasing climate and health knowledge; thus, we developed several educational initiatives. In this viewpoint, we discuss our process for conducting environmental scans, building capacity and partnerships, and translating knowledge-to-action around climate and health.